Compartmentalization of Inflammatory Response Following Gut Ischemia Reperfusion. Issue 1 (January 2015) - Collange, O.; Charles, A.-L.; Lavaux, T.; Noll, E.; Bouitbir, J.; Zoll, J.; Chakfé, N.; Mertes, M.; Geny, B.
<x xml:space="preserve">Abstract</x> Objective/background Gut ischemia reperfusion (IR) is thought to trigger systemic inflammation, multiple organ failure, and death. The aim of this study was to investigate inflammatory responses in blood and in two target organs after gut IR. Methods This was a controlled animal study. Adult male Wistar rats were randomized into two groups of eight rats: control group and gut IR group (60 minutes of superior mesenteric artery occlusion followed by 60 minutes of reperfusion). Lactate and four cytokines (tumor necrosis factor-α, interleukin [IL]-1β, IL-6, and IL-10) were measured in mesenteric and systemic blood. The relative gene expression of these cytokines was determined by real time polymerase chain reaction in the gut, liver, and lung. Results Gut IR significantly increased lactate levels in mesenteric (0.9 ± 0.4 vs. 3.7 ± 1.8 mmol/L; p < .001) and in systemic blood (1.3 ± 0.2 vs. 4.0 ± 0.3 mmol/L; p < .001). Gut IR also increased the levels of four cytokines in mesenteric and systemic blood. IL-6 and IL-10 were the main circulating cytokines; there were no significant differences between mesenteric and systemic cytokine levels. IL-10 was upregulated mainly in the lung, suggesting that this organ could play a major role during gut reperfusion. Conclusion The predominance of IL-10 over other cytokines in plasma and the dissimilar organ responses, especially of the lung, might be a basis for the design of therapies, for example lung protective ventilation strategies, to limit the deleterious effects of the inflammatory cascade. A multi-organ protective approach might involve gut directed therapies, protective ventilation, hemodynamic optimization, and hydric balance.